Cerebral salt wasting after traumatic brain injury: a review of the literature. Issue 1 (December 2015) - Leonard, Jan; Garrett, Raymond; Salottolo, Kristin; Slone, Denetta; Mains, Charles; Carrick, Matthew; Bar-Or, David
Abstract Electrolyte imbalances are common among patients with traumatic brain injury (TBI). Cerebral salt wasting (CSW) is an electrolyte imbalance characterized by hyponatremia and hypovolemia. Differentiating the syndrome of inappropriate antidiuretic hormone and CSW remains difficult and the pathophysiological mechanisms underlying CSW are unclear. Our intent was to review the literature on CSW within the TBI population, in order to report the incidence and timing of CSW after TBI, examine outcomes, and summarize the biochemical changes in patients who developed CSW. We searched MEDLINE through 2014, hand-reviewed citations, and searched abstracts from the American Association for the Surgery of Trauma (2003–2014). Publications were included if they were conducted within a TBI population, presented original data, and diagnosed CSW. Publications were excluded if they were review articles, discussed hyponatremia but did not differentiate the etiology causing hyponatremia, or presented cases with chronic disease. Fifteen of the 47 publications reviewed met the selection criteria; nine (60 %) were case reports, five (33 %) were prospective and 1 (7 %) was a retrospective study. Incidence of CSW varied between 0.8 - 34.6 %. The populations studied were heterogeneous and the criteria used to define hyponatremia and CSW varied. Though believed to play a role in the development of CSW, increased levels of natriuretic peptides in patients diagnosed with CSW were not consistently reported. These findings reinforce the elusiveness of the CSW diagnosis and the need for strict and consistent diagnostic criteria.